A remarkable new genus of Nirvanini (Hemiptera: Cicadellidae: Evacanthinae) from Southeast Asia - Dietrich, C. H. (Zootaxa, 2011)
Draconirvana, gen. n., is described and illustrated based on a single new species D. siamensis, from Thailand. The new genus is morphologically intermediate between Evacanthini and Nirvanini but is placed in the latter tribe based on its depressed form and the incomplete longitudinal carina on the face.